Brazil in the face of new SARS-CoV-2 variants: emergencies and challenges in public health - Marquitti, Flavia Maria Darcie; Coutinho, Renato Mendes; Ferreira, Leonardo Souto [UNESP]; Borges, Marcelo Eduardo; Portella, Tatiana Pineda; Silva, Rafael Lopes Paixão Da [UNESP]; Canton, Otavio [UNESP]; Poloni, Silas [UNESP]; Franco, Caroline [UNESP]; Coelho, Verônica; Barberia, Lorena; Bolle, Monica De; et al. (Associação Brasileira de Saúde Coletiva, 2021)
This article discusses the epidemic situation of Covid-19 in Brazil, in the face of the emergence of a new strain called P.1, which is more transmissible and may be associated with reinfection. Given the collapse of hospital care in Manaus in January 2021 and the results of three recent preprints, each that reports increased transmissibility of the P.1 variant, we propose some urgent measures. Genomic surveillance based on multi-step diagnostics, starting with RT-PCR type tests and up to sequencing, should be established. Efforts to identify reinfections associated with this variant and the update of its definition in protocols should be prioritized, and studies on the efficacy of currently available vaccines in Brazil concerning the new variant should be conducted. We also propose improving the Brazilian health surveillance system such that genomic surveillance is coordinated and thereby better able to respond to future emergencies in a more timely fashion. We call on the public agents involved in health surveillance to share data and information regarding the epidemic in a clear, fast and transparent way. Finally, we propose a greater engagement in inter-institutional cooperation of all those involved in the response and production of knowledge about the pandemic in our country.
Keywords: Coronavirus infections; Surveillance; Epidemics